Product Expansion dari Endowment Factor Pepaya Desa Mayangan Kecamatan Gumukmas Kabupaten Jember - Lilis Yuliati; Siti Komariah; Moh. Adenan (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The activity service aims to increase the productivity of the "Bolo Dewo". Partners located in the Muneng Hamlet RT. 02 RW. 03 and RT. 04 RW. 03, Mayangan Village, Gumukman District, Jember Regency, East Java. They have a papaya-based food processing business, which is abundant in the village. The implementation team offers a solution to solve the Partner's problem, thereby affecting the increase in family income in particular and the village economy in general. The solution was, the Implementation Team bought a set of tools in the form of a cup sealer machine, which could be used to package the Candied Carica Papaya. The results of the implementation of this service are: 1) diversifying papaya processed products into Candied Carica Papaya, which is a fresh drink in a package that many children like to remember sweet, sour, and fresh when consumed in cold conditions; 2) provide a set of tools in the form of a cup sealer used to package drinks in a cup; 3) screen printing design /branding cup cover permanently; 4) help from the marketing aspect by loading on youtube, so that the product is known to many people.